The intuitive compass : why the best decisions balance reason and instinct - Cholle, Francis P., 1965- (San Francisco : Jossey-Bass, 2012)
'A dynamic new way to understand intuition, already implemented around the world at top companies and business schools. Neuroscience shows that instinct has a leading role in complex decision-making, yet imaginative play is the most direct means of activating our creativity and problem-solving abilities. Based on over 20 years of Cholle's wide-ranging professional experience and insights, The Intuitive Compass offers a fascinating new approach to innovative problem-solving, decision-making, and sustainable value creation. Through a concept known as Intuitive Intelligence, Cholle shows how anyone can improve creative brainpower by harnessing the balance between reason and instinct. Explores the tension between linear efficiency and random play, and the synergy between reason and instinct Helps us realize our natural tendencies to think holistically, think paradoxically, notice the unusual, or lead by influence Shows these tenets in action through case studies of the luxury house Hermes, Paris; Google and its paradoxical work culture; Virgin America, and its ability to notice the unusual about what matters for consumers and exert leadership in its industry The Intuitive Compass shows how to thrive within chaos and offers actionable information for reinventing our path to sustainable success'--
Includes bibliographical references and index.
Keywords: Intuition; Problem solving; Decision making; BUSINESS & ECONOMICS / Leadership